2012
DOI: 10.1016/j.nut.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and food intake in patients with systemic lupus erythematosus

Abstract: The results showed that patients with SLE have inadequate nutritional status and food intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 26 publications
2
50
1
9
Order By: Relevance
“…Although several studies have reported the positive correlation between obesity and a higher prevalence or worse prognosis of SLE [6,7,35,37], to our knowledge, this is the first study to demonstrate that the SLE onset is influenced by weight gain and is preceded by an increase in ROS production by blood neutrophils.…”
Section: Discussionmentioning
confidence: 63%
“…Although several studies have reported the positive correlation between obesity and a higher prevalence or worse prognosis of SLE [6,7,35,37], to our knowledge, this is the first study to demonstrate that the SLE onset is influenced by weight gain and is preceded by an increase in ROS production by blood neutrophils.…”
Section: Discussionmentioning
confidence: 63%
“…AND/ASPEN considers that if ≥2 of the following 6 characteristics are present, the patient is malnourished: insufficient energy intake, weight loss, loss of muscle mass, loss of subcutaneous fat, localized or generalized fluid accumulation that may sometimes mask weight loss, and diminished functional status as measured by handgrip strength. In addition, several authors have compared these 2 tools with other used instruments that provide the diagnosis and predict morbidity, mortality, length of stay, and costs …”
Section: Nutrition Assessmentmentioning
confidence: 99%
“…Elevated IL-37 levels in humans are generally found in patients with inflammatory diseases such as nonallergic asthma [32] and systemic lupus erythematosus (SLE) [33]. SLE patients have indeed been reported to have inadequate food intake [34], which would be consistent with higher IL-37, but the complexity and versatility of the immune system makes it challenging to attribute this effect to a specific inflammatory component. Recent genetic studies on body mass index revealed that a majority of the tissues and cell types in which genes near BMI-associated SNPs are highly expressed, are part of the central nervous system [35].…”
Section: Discussionmentioning
confidence: 99%